Contrasting Weather and Stocking Effects on Eucalyptus Initial Coppice Response in Brazil - Fernandes, Pietro Gragnolati; Alvares, Clayton Alcarde [UNESP]; Queiroz, Túlio Barroso [UNESP]; Pimenta, Pedro Vitor; Borges, Jarbas Silva; Stahl, James; Mendes, Flávio Teixeira; Souza, Amanda; Silva, Gustavo Matheus; da Silva, Gualter Guenther Costa; Milhomem, Sara Bezerra Bandeira; Sousa, Rosilvam Ramos de; et al. (MDPI, 2024)
In Eucalyptus plantations, coppice rotations often yield less than initial rotations. The TECHS project (Tolerance of Eucalyptus Clones to Hydric, Thermal and Biotic Stresses) studied short rotation coppicing across a 3000 km gradient. The main objective of this work was to compare the survival, sprouting, and initial growth of Eucalyptus clones managed and to examine factors that might influence the productivity of the coppice rotation: climate, genotypes, and stocking. Eight of the TECHS sites spread from latitudes 6° S to 30° S were included in the coppice study, with 17 genotypes at each site. The initial rotation had been planted at a 3 m × 3 m spacing and also in a spacing trial at densities from 500 to 3500 trees ha−1. Six months after harvesting the initial Eucalyptus rotation, average survival was 88%, with tropical clones showing over twice the sprouting biomass (6.7 vs. 2.9 Mg ha−1) and four times the woody biomass compared to subtropical clones (4.7 vs. 1.1 Mg ha−1). Greater initial water deficits had stronger sprouting and growth. Clones with higher belowground carbon allocation in the initial rotation performed better in coppicing, and precipitation became more influential after 12 months. Drought and spacing trials significantly affected growth.
Keywords: climate gradient; initial growth; productivity; silviculture